Effect of fire exposure on cracking, spalling and residual strength of fly ash geopolymer concrete - Sarker, Prabir; Kelly, S.; Yao, Z. (Elsevier Ltd, 2014)
Fly ash based geopolymer is an emerging alternative binder to cement for making concrete. The cracking, spalling and residual strength behaviours of geopolymer concrete were studied in order to understand its fire endurance, which is essential for its use as a building material. Fly ash based geopolymer and ordinary portland cement (OPC) concrete cylinder specimens were exposed to fires at different temperatures up to 1000 °C, with a heating rate of that given in the International Standards Organization (ISO) 834 standard. Compressive strength of the concretes varied in the range of 39–58 MPa. After the fire exposures, the geopolymer concrete specimens were found to suffer less damage in terms of cracking than the OPC concrete specimens. The OPC concrete cylinders suffered severe spalling for 800 and 1000 °C exposures, while there was no spalling in the geopolymer concrete specimens. The geopolymer concrete specimens generally retained higher strength than the OPC concrete specimens. The Scanning Electron Microscope (SEM) images of geopolymer concrete showed continued densification of the microstructure with the increase of fire temperature. The strength loss in the geopolymer concrete specimens was mainly because of the difference between the thermal expansions of geopolymer matrix and the aggregates.